Art as craft in the writings of AS Byatt: a study of Byatt's use of devices of metafiction (intertext and autotext) to examine how women transgress the conventions of male-ordered society in their efforts to exercise their creativity and converse with the world - Rogers, Susan (Department of English Language and Literature, 2024)
This examination of how AS Byatt has used the central female characters of Possession (LaMotte) and Babel Tower (Frederica Potter) to explore the stifling effects of the institutions and conventions of male-ordered society on creative women, is undertaken in two parts. The first chapter considers the intertextual creation of Possession's LaMotte from the biography and canon of the American Victorian poet Emily Dickinson. Both the fictive and the real-life poets, possessed by a creative talent, frustrated by its lukewarm reception and disempowered by their inferior status, withdrew from society. The second chapter considers the commentary offered by autotext (extracts from the fantasy tales Babbletower and Flight North) on the emotional and intellectual development of Babel Tower's Frederica, who seeks to live by what she learns from reading and analysing literature. (Autotextual writing comments on LaMotte's story too, for the fairy tale 'The Glass Coffin' resonates within its framing text, Possession.) Elements of fairy tale in Frederica's story self-consciously highlight the novel's status as fiction, reminding readers that they, like Frederica, are a construction of what they read and experience. Nineteenth-century LaMotte withdraws from society with the financial co-operation and emotional support of a female companion, defying social pressure exerted on her to marry and produce children rather than poetry. This withdrawal grants her dignity and independence. However, a brief liaison with a married poet triggers a second withdrawal for patriarchal conditioning has taught her to regard her actions as transgression and she colludes with this judgement. This second withdrawal is destructive for it leaves her embittered and condemned to obscurity. Twentieth-century Frederica is enraged by the limitations against which she chafes as wife and mother. She abandons her husband and his home and establishes her emotional and financial independence. Frederica successfully defies convention because in her century restrictions have been eased on women's movements, actions and occupations. Byatt represents in both LaMotte and Frederica her view of her own art as craft diligently practised and essential to the emotional well-being of the artist. In her characters' lives and experience she explores her own fear that her gender might thwart her ambition, no matter how great her talent. An examination of Byatt's essays and interviews on the subject of her craft reveals her private imagery of the construction of a novel. She compares her art to the precise and exquisite craft of tapestry-weaving or of a spider spinning: it is pleasing and intricate. Images of spinning and sewing/weaving are evident in the work of both fictitious LaMotte and real-life Dickinson. In twentieth-century Frederica's life these images are given a new spin: with maturity and experience, Frederica perceives how her reading has led her to seek connection which she abhors. She subsequently learns to record her experiences, whether in memory or in writing, in self-contained layers so that they are ordered and preserved but not interwoven; this gives her a sense of freedom. She adopts a personal metaphor to describe this process: laminations. Thus these two novels are pervaded by Byatt's personal vision: art as craft.